The expression n = a ∑ ∞ b = n ∑ ∞ ( n − a ) ! ( b − n ) ! 1 , for a , b , n ∈ N , can be expressed as k 2 . Find k .
Try my other calculus challenges here
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think that the index summation is also incorrect. Likely what he wanted was
n = a ∑ ∞ m = b ∑ ∞ ( n − a ) ! ( m − b ) ! 1
Log in to reply
Oh, excuse me, I will edit the problem..Sorry for that mistake.
Sorry, I did not understand how did you get n ! 1 from ( n − a ) ! 1 ?
Problem Loading...
Note Loading...
Set Loading...
Assuming that the question meant n = a ∑ ∞ b = n ∑ ∞ ( n − a ) ! ( b − n ) ! 1 We can solve this problem. First start by pulling out the 1 / ( n − a ) ! part and manipulating indexes n = a ∑ ∞ b = n ∑ ∞ ( n − a ) ! ( b − n ) ! 1 = n = a ∑ ∞ ( n − a ) ! 1 b = n ∑ ∞ ( b − n ) ! 1 = n − a = 0 ∑ ∞ ( n − a ) ! 1 b − n = 0 ∑ ∞ ( b − n ) ! 1 = n = 0 ∑ ∞ n ! 1 k = 0 ∑ ∞ k ! 1 = e ⋅ e = e 2 Thus the answer is e ≈ 2 . 7 1 8